161k views
5 votes
What is the function rule represented by the following table? x y 0 0 1 -2 -2 4 y = -x - 1 y = -2x y = x - 3 y = -3x + 2

User IronSean
by
4.9k points

2 Answers

2 votes

Answer:

y = -2 x - 1

Explanation:

User Horen
by
5.7k points
4 votes

Answer:


y = -2x

Explanation:

Given

x || 0 || 1 || -2

y || 0 || -2 || 4

Required

Determine the function rule

First, we have to determine the slope of the function using;


m = (y_1 - y_2)/(x_1 - x_2)

Where x and y represent any two corresponding values of x and y

When x = 0; y = 0
(x_1,y_1)

When x = 1; y = -2
(x_2,y_2)

Substitute these values in
m = (y_1 - y_2)/(x_1 - x_2)


m = (0 - (-2))/(0 - 1)


m = (0 +2)/(0 - 1)


m = (2)/(- 1)


m = -2

Next, is to determine the function rule; using slope intercept form as follows;


y - y_1 = m(x - x_1)

Take any corresponding values of x and y as x1 and x2

When x = -2; y = 4


y - y_1 = m(x - x_1) becomes


y - 4 = -2(x - (-2))


y - 4 = -2(x + 2)

Open the bracket


y - 4 = -2x -4

Add 4 to both sides


y - 4 + 4 = -2x - 4 + 4


y = -2x

Hence, the function rule is
y = -2x

User Khanh Hua
by
5.2k points